2017
DOI: 10.1038/s41598-017-13664-x
|View full text |Cite
|
Sign up to set email alerts
|

Regiospecific Synthesis of Ring A Fused Withaferin A Isoxazoline Analogues: Induction of Premature Senescence by W-2b in Proliferating Cancer Cells

Abstract: Induction of premature senescence represents a novel functional strategy to curb the uncontrolled proliferation of malignant cancer cells. This study unveils the regiospecific synthesis of novel isoxazoline derivatives condensed to ring A of medicinal plant product Withaferin-A. Intriguingly, the cis fused products with β-oriented hydrogen exhibited excellent cytotoxic activities against proliferating human breast cancer MCF7 and colorectal cancer HCT-116 cells. The most potent derivative W-2b triggered premat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…280 Reaction of withaferin A with various N-hydroxy benzenecarboximidoyl chlorides led to the regiospecic synthesis of a series of novel isoxazoline derivatives, which were condensed into ring A (627-643). 281 Considering the steric interactions with 4,5,10-substituents, a large number of stereoisomers with a b,bring juncture were obtained. Similarly, another attempt to semisynthesize isoxazilidino withaferin was made via two-step reaction of nitrone synthesis and nitrone 1,3-dipolar cycloaddition yielding highly chemoselective and diastereoselective cisfused products (644-647).…”
Section: Reviewmentioning
confidence: 99%
“…280 Reaction of withaferin A with various N-hydroxy benzenecarboximidoyl chlorides led to the regiospecic synthesis of a series of novel isoxazoline derivatives, which were condensed into ring A (627-643). 281 Considering the steric interactions with 4,5,10-substituents, a large number of stereoisomers with a b,bring juncture were obtained. Similarly, another attempt to semisynthesize isoxazilidino withaferin was made via two-step reaction of nitrone synthesis and nitrone 1,3-dipolar cycloaddition yielding highly chemoselective and diastereoselective cisfused products (644-647).…”
Section: Reviewmentioning
confidence: 99%
“…In addition, acetate derivatives of WA were also more active than WA—di- and tri- acetate analogs 130e and 131 were shown to be relatively more potent, with IC 50 values ranging 0.11 μM to 0.65 μM compared to monoacetate analogs 130a , 130b , and 130c , having IC 50 values of 0.415–3.06 μM against head and neck squamous cell (HNSCC, JMAR), breast cancer cells (MDA-MB-231), melanoma (SKMEL-28) and colon cancer (DRO81-1) cells [ 114 ]. Among the A-ring-fused isoxazolines, WA analogs, the compounds having a nitro group and β,β ring juncture (e.g., 138 ), were shown to be more active than the α,α ring juncture (e.g., 139) against MCF-7 and HCT-116 cell lines [ 119 ]. A recent report from our group indicates that C4-acetylated analog ASR490 ( 116 ) of WA was significantly more potent than WA in inducing apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Faheem Rasool group synthesized novel withaferin A-ring-condensed, 2-isoxazoline derivatives [ 119 ]. The rationale for designing 2-isoxazoline-fused withanolides was that this moiety has been known as a building block for biologically active molecules and an essential precursor in organic reactions [ 120 ].…”
Section: Withanolides As Anti-cancer Agentsmentioning
confidence: 99%
“…Nuclear factor-κB (NF-κB) is an important nuclear transcription factor and is found in almost all mammalian cells, which is involved in inflammatory and immune responses and regulation of apoptosis and cellular stress [31]. Chen et al found that NF-κB activity was related to hepatocytes apoptosis [32].…”
Section: Fig 6 Effect Of Iκbα/nf-κb In Mice With Acute Liver Injurymentioning
confidence: 99%